Complex Analytical Fiber Over Non-Compact Riemann Surfaces - Eltahir, Amna Eltahir Mokhtar; Abdel Rahman, Abdel-Radi Abdel-Rahman Abdel-Gadir (European Journal of Applied Sciences, 2024)
In this paper we explained the Complex Analytical Fiber Over Non-Compact Riemann Surface. We aimed to a relation between Complex analytic, Riemann Surfaces and Riemann Hilbert problems. The Compact Complex Surface S to a Riemann surface B such that the general fiber off is a Riemann surface of genus g. and singular for Riemann Hilbert problems.